Does Shariah committee composition influence Shariah governance disclosure? evidence from Malaysian Islamic banks - Noordin, Nazrul Hazizi (Emerald Publishing, 2019)
Abstract Purpose – The purpose of this paper is to investigate the empirical linkage between the composition of Shariah Committee and the extent of Shariah governance disclosure in 16 licensed Islamic banks in Malaysia. Design/methodology/approach – This paper adopted a multiple regression analysis to test the association between the composition of Shariah Committee and the extent of Shariah governance disclosure. A disclosure index was developed to measure the extent of Shariah governance disclosure made by the Islamic banks. Whereas to measure the extent of Shariah governance disclosure, this study used content analysis as a method of coding qualitative information in the annual reports. Findings – Using 2009 data, the study found a significant association between different compositions of the Shariah Committee in the Malaysian Islamic banks and their Shariah governance disclosure level before the introduction of the Shariah Governance Framework (SGF). However, because of less variation in the composition of Shariah Committee after the introduction of SGF 2010, a weak linkage was found between the composition of ShariahCommittee and the extent of Shariah disclosure of Malaysian Islamic banks in 2013. Research limitations/implications – Findings of this study offer several implications for further improvements of the Malaysian Islamic banking sector in particular, and other Islamic banks globally. As better composition of Shariah Committee in terms of its size, academic background and other relevant expertise would result in effective monitoring system leading to better practices of Shariah disclosure, this finding highlights the relevance and important role of the Shariah Committee in improving voluntary Shariah disclosure level of the Islamic banks. This finding suggests that ample focus has to be channelled in strengthening the composition of Shariah Committee in crafting future development of SGF in Malaysia. It is also suggested that Islamic banks need to give priority in providing more education and training in various areas of expertise to their Shariah Committee members that would result in greater confidence of investors, stakeholders and the society on the information disclosed by the banks. Originality/value – The novelty of this paper lies in highlighting the importance of different composition of Shariah Committee in determining the extent of voluntary disclosure made on Shariah matters by the Islamic banks.